Training of The Utilization of Medicinal Plants as Complementary Medicine Among Health Workers - Haerawati Idris; Dian Safriantini; Tia Sabrina (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
The current community service focused on the use medicinal plants which seemed to increase among families. This program was supported by the 2018 Riskesdas report, which showed that 38.7% of Indonesia’s population had used traditional medicine for treatments. This program sought to discover health workers’ knowledge of family medicinal plant training. This community service was carried out through the mentoring method and involved 25 public health center employees representing each primary healthcare in Ogan Ilir Regency. We selected the sample using the total sampling method. The mentoring session was organized in the form of training related to the concepts of family medicinal plants and how to use them. This training involved a number of lectures and presentations of a model of family medicinal plants. The diﬀerences in knowledge of the training participants were measured using a pretest and posttest. The data were analyzed using the t-test. The results showed a diﬀerence in health workers’ knowledge before and after the training (p <0.05). There is an increase in the knowledge of primary healthcare workers regarding family medicinal plants.